A língua própria do surdo : a defesa da língua a partir de uma subjetividade surda resistente - Nascimento, Gabriel Silva (2019)
“The deaf own language: language advocacy based on a resistant deaf subjectivity” forthcoming, addresses a research embracing deaf education and sign language, whose overall objective aims to investigate what has been taken as “language status” and sign language in a national context. The work assumes an archeological envisioning investigation of the Libras as a property of a specific group. It embodies a documental-bibliographical research, taking as basic sources, the analysis of historical documents, specially the recordings of the Deaf Congress in Paris (1900) along with classic books the underlid the Brazilian researches for the past two decades in two lines: sign language and deaf culture. The theoretical framework grounds the work of Michel Foucault, deploying the experience matrix as the theoretical-methodologic tool and the axes of knowledge, power and ethics as analytical lenses. Reviewing the past through an archaeological approach, presents as a valid quest to understand the discursive practices taking shapes nowadays. It seems necessary to consider the historical and economic contexts that produces this wisdom, understand their national, cultural and linguistic ties, as well as the investments towards education regarding both deaf and hearing people. Given the competition arena where Libras and Portuguese create boundary relations, we intend to discuss how much reducing a language to a specific community property makes it vulnerable or strengthened, when the goal is to achieve a bilingual social organization. The considerations allow us to uncover a third way to advocate language, parallel to the Linguistics and Cultural studies, entailing a resistant deaf subjectivity demeanor that may risk suggesting monolingual life ways unlike the intentions of the bilingual movements and its claim for the social recognition of Libras.